Towards sustainable retirement planning of wageworkers in Thailand: A qualitative approach in behavioral segmentation and financial pain point identification - Chavis Ketkaew; Martnine Van Wouwe; Ann Jorissen; Danny Cassimon; Preecha Vichitthamaros; Sasichakorn Wongsaichia (Risks, 2022)
Thailand recently reached "aged" society status, signifying that over twenty percent of the population is over sixty. Considering that Thailand has a low literacy rate, a fractured pension system, and no regulations that could provide sufficient income to cover basic needs after retirement, there will be economic repercussions if the situation is not handled soon. The government and financial institutions have been encouraging Thai citizens to prepare retirement plans but lack understanding of the root causes of being unprepared for retirement. The objectives of this qualitative research were to explore the behavior, knowledge, and preparedness towards retirement in governmental and private wageworkers. Moreover, the study aims to identify the pain points of being unprepared for retirement and deliver the optimal solutions and sustainable retirement plans suitable for each segment. This article employed a sample of 46 wageworkers in Khon Kaen, Thailand with ages ranging from 20 to 59 years old. Qualitative semi-structured in-depth interviews and qualitative content analysis were conducted with the respondents asking about their income, expenses, pains, and problems towards saving for retirement, their desired outcome after they retire, and how they would achieve it. The framework used for the in-depth qualitative interview was by utilizing the customer, problem, and solution zoom tool. The research contributions were to facilitate Thai citizens being ready for retirement stages and overcome post-retirement risks sustainably. The results revealed that the sample could be divided into four segments by their characteristics. Two low-income segments share the same traits and behaviors that can prove that financial literacy plays an essential role in retirement readiness. Lower-income wage workers do not have their money put in place to prepare for retirement. Additionally, this article discussed the study's implications for wageworkers, employers, and the Thai government. This article recommended that Thai citizens should accumulate wealth in various ways, including investment in financial assets and earning additional income from a second job. Employers should provide suitable retirement contribution schemes. The government should launch a policy enabling above-60-year-old seniors to continue working.
Keywords: 330; retirement readiness; pension system; financial behavior; financial literacy; sustainable retirement planning